Short-Term Seismic Precursors to Icelandic Eruptions 1973–2014 - Einarsson, Páll (Frontiers in Earth Science, 2018)
Networks of seismographs of high sensitivity have been in use in the vicinity of active volcanoes in Iceland since 1973. During this time 21 confirmed eruptions have occurred and several intrusions where magma did not reach the surface. All these events have been accompanied by characteristic seismic activity. Long-term precursory activity is characterised by low-level, persistent seismicity (months-years), clustered around an inflating magma body. Whether or not a magma accumulation is accompanied by seismicity depends on the tectonic setting, interplate or intraplate, the depth of magma accumulation, the previous history and the state of stress. All eruptions during the time of observation had a detectable short-term seismic precursor marking the time of dike propagation towards the surface. The precursor times varied between 15 minutes and 13 days. In half of the cases the precursor time was less than 2 hours. Three eruptions stand out for their long duration of the immediate precursory activity, Heimaey 1973 with 30 hours, Gjálp 1996 with 34 hours, and Bárðarbunga 2014 with 13 days. In the case of Heimaey the long time is most likely the consequence of the great depth of the magma source, 15-25 km. The Gjálp eruption had a prelude that was unusual in many respects. The long propagation time may have resulted from a complicated triggering scenario involving more than one magma chamber. The Bárðarbunga eruption at Holuhraun issued from the distal end of a dike that took 13 days to propagate laterally for 48 km before it opened to the surface. Out of the 21 detected precursors 14 were noticed soon enough to lead to a public warning of the coming eruption. In 4 additional cases the precursory signal was noticed before the eruption was seen. In only 3 cases was the eruption seen or detected before the seismic precursor was verified.